Test results of a REBCO superconducting switch for reducing temporal fluctuations in driven-mode. (June 2020) - Iwai, S; Otani, Y; Miyazaki, H; Tosaka, T; Nomura, S; Ito, T
Abstract: High-temperature superconducting magnets are generally driven by a power supply (driven mode), and temporal fluctuations of the power supply unit, such as ripple noise, directly affect the magnetic field stability. A method of suppressing such temporal instability by short-circuiting both ends of the coil with finite low-resistance joints, somewhat similar to a persistent current switch, has been proposed in order to form a closed loop having a large time constant, L/R . In this research, we developed two types of REBCO superconducting switches was constructed with a non-inductive winding using mainly ordinary copper-coated REBCO tapes, and type-B switch used uncoated REBCO tapes toward application to emergency shutdown. For the type-B switch, at the end of the winding, copper-coated REBCO tapes were jointed to prevent degradation by exposure to moisture. The R-T and V-I characteristics of each switch when cooled with liquid nitrogen were tested. The type-A switch was applied to a test REBCO magnet, and the temporal stability of the magnetic field was evaluated under a conduction cooling configuration in the driven mode.